Respuesta :

Answer:

-1

Step-by-step explanation:

k + (2k - 10) =

= 3 + (2 * 3 - 10)

= 3 + (6 - 10)

= 3 + (-4)

= -1

Answer:

The value of the equation is -1

Step-by-step explanation:

1st plug in 3 in the equation for k

3 + (2(3)-10)

now we can use PEMDAS

3 + (6 - 10)

we multiplied 2 and 3 to get 6

keep going

3 + -4

now that you have this, we can solve with intervals

btw A positive - negative becomes a negative symbol -

so your equation looks like this now

3 - 4

now we can subtract and our final answer should be

-1

High Hopes <3

Barry